1983
DOI: 10.1007/bf01544046
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of myogenesis by somatic cell hybridization: III. Myogenic competence of hybrids derived from rat L6 myoblasts and mouse primary fibroblasts and myoblasts

Abstract: Hybrid cells derived from rat L6 myoblasts and mouse primary fibroblasts (M x F hybrids), as well as those derived from rat L6 myoblasts and mouse primary myoblasts (M x M hybrids), were examined for their ability to engage in myogenesis as judged by muscle fiber formation plus the expression of skeletal muscle myosin and creatine kinase (CK). Of 172 primary hybrid colonies scored, 59% were myogenic in the M x F fusion and 97% exhibited muscle fiber formation in the M x M fusion. Individual hybrid clones from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1983
1983
1984
1984

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
0
1
Order By: Relevance
“…Our results differ from two recent reports involving myogenic cell hybrids (33,34). Lawrence and Coleman found that hybrids between competent and differentiation-defective L6 myoblasts exhibited high rather than intermediate levels ofdifferentiation (33).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results differ from two recent reports involving myogenic cell hybrids (33,34). Lawrence and Coleman found that hybrids between competent and differentiation-defective L6 myoblasts exhibited high rather than intermediate levels ofdifferentiation (33).…”
Section: Discussioncontrasting
confidence: 99%